EXAMINING PATHWAYS TO CUSTOMER LOYALTY IN BEAUTY CLINICS: A STRUCTURAL EQUATION MODELING APPROACH WITH SATISFACTION AS A MEDIATOR AND INTIMACY AS A MODERATOR - Kamiluddin; Vanessa Gaffar; Ratih Hurriyati; Hilda Monoarfa (POLITEKNIK LP3I JAKARTA, 2026)
Customer loyalty is a critical determinant of long-term competitiveness in beauty clinics and aesthetic healthcare services. Despite a growing body of research, the structural pathways through which service quality and customer experience influence customer loyalty remain theoretically fragmented. The psychological mechanisms that link these antecedents to loyal behavior, particularly the mediating role of customer satisfaction and the moderating role of service intimacy, have not been simultaneously examined in an integrated framework specific to beauty clinic settings. This systematic literature review addresses that gap by synthesizing 19 peer-reviewed studies selected through the PRISMA 2020 framework from Scopus-indexed publications between 2020 and 2026. Thematic synthesis revealed three principal findings. First, customer satisfaction consistently and strongly mediates the effects of both service quality and customer experience on customer loyalty. Second, customer experience is a multidimensional construct encompassing cognitive, emotional, sensory, relational, and digital dimensions of the patient journey. Third, service intimacy amplifies the satisfaction-to-loyalty conversion by deepening trust, emotional attachment, and personalized care between patients and practitioners. The novelty of this review lies in its proposal of an integrated moderated mediation framework that positions service intimacy as a relational boundary condition within a unified loyalty model for aesthetic healthcare, a configuration that has not previously appeared in the literature.